PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA, MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA LPD DESA ADAT SIBANGGEDE - Gde Bayu Surya Parwita; Made Ika Prastyadewi; Ni Luh Opik Mahena Dewi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Human resources are a very important factor in determining the achievement of an organization. Companies need potential human resources, both leaders and employees, in the pattern of tasks and supervision, which determine the achievement of company goals. Good employee performance is a step to achieving organizational goals. So efforts need to be made to improve employee performance. This study aims to determine the influence of leadership style transformationa,l work environment, work motivation towards employee performance at LPD Desa Adat Sibanggede. This research was conducted at LPD Desa Adat Sibanggede. The sample in this study was 35 employees. The analysis techniques used are multiple linear regression analysis, validity test, reality test, classical assumption test, multiple correlation analysis, determination coefficient analysis, f test and t test through SPSS program version 25. Based on the results of the analysis, this study shows that the leadership style Transformational has a positive and significant effect on employee performance at LPD Desa Adat Sibanggede. The work environment has a positive and significant effect on employee performance at LPD Desa Adat Sibanggede. Work motivation has a positive and significant effect on employee performance at LPD Desa Adat Sibanggede.